The impact of family group decision-making on preventing removals. (July 2017) - Lambert, Matthew C.; Johnson, Leah E.; Wang, Eugene W.
Highlights: This study used structural equation modeling to analyze over 600, 000 investigation cases spanning a five-year period Cases where the mother was a teenager and cases with higher risk scores demonstrated a greater likelihood to include a Family Team Meeting as part of the investigation process Family Team Meetings had an substantial effect on child welfare investigation outcomes even after controlling for other pertinent covariates The odds of removal from the home reduced by 51.4% for children who had a Family Team Meeting